ANALISIS NUMERIK UNTUK MEMPREDIKSI DAYA DUKUNG PONDASI DANGKAL PADA TANAH LUNAK DENGAN DAYA DUKUNG RENDAH - Elvirandra, Laura; Hamzah Fansuri, Muhammad; Dharma Saputra, Pungky; Hasanah, Mauliyatul; Citra Asokawati, Fajrina (Construction and Material Journal, 2024)
This research aims to determine the types and dimensions of shallow foundations that are effectively used on difficult soils with low bearing capacity. The selection of foundation types and dimensions is based on the allowable ultimate bearing capacity to support the superstructure of a building. The analysis used Terzaghi's theory with Standard Penetration Test data. This study used a size of 0.30 m in width and 1.0 m in length. The groundwater table is located 6.0 meters from the ground surface. The next variations of width are 0.35 m and 0.4 m. Results of this study show that the most effective type of foundation was a palm foundation type with a width of 0.4 m. The analysis indicated that the width of the foundation was 0.4 m, and the groundwater level was 1.0 m below the base. The ultimate bearing capacity value is 148.16 kN/m²; the carrying capacity of the permit was 49.39 kN/m² with a column total load of 19.76 kN.